(untitled) (Journal of actual problems of jurisprudence, 2019)
In this articlethe author describes the classification of measures of criminal procedure compulsion. There are given a number of classifications of the coercive procedural measures, the measures of criminal procedure compulsion: depending on a subject, which rights can be affected as a result of application of these measures, and depending on the degree of limitation of rights and individual freedoms, and depending on the aim of application. Key words: criminal procedure, the classification, measures of criminal procedure, detention, measures of suppression, judicial compulsion.